β – Thalassemia with Pregnancy Women - Boonyakiat, Somboon (วารสารพยาบาลเกื้อการุณย์, 2015)
The objective of this paper is to study beta thalassemia in pregnant women. Beta thalassemia is a genetic blood disease which is categorised into three degrees of severity: mild, moderate and severe forms. A screening test for pregnant women and couples is important. If a couple has a genetic blood disease, thalassemia will be passed from parents to child in genes. For example, if both parents are carriers of β- thalassemia trait (B0/B), 1/4 risk of having homozygous β- thalassemia (B0/B0) which is a severe blood disease (β- thalassemia major) will inherit. If a woman has β- thalassemia trait (B0/B) but her partner has Hb E trait (BE/B) or homozygous Hb E (BE/BE), their children may inherit a 1/4 or 2/4 of β –thalassemia /Hb E disease (B0/BE) which is moderate severity (thalassemia intermediate) respectively. Nursing roles for pregnant women with β- thalassemia are psychological care to reduce their stress such as anxiety and grief, including thalassemia counselling and educating such as maternal and child effects, decision making for the next pregnancy and self care.